Global dynamics of a predator-prey model incorporating a constant prey refuge - Xiaolei Yu; Fuqin Sun (Electronic Journal of Differential Equations, 2013)
In this article, a general predator-prey model incorporating a constant prey refuge with Hassell-Varley type functional response is studied. Sufficient conditions for the stability of the equilibria are obtained. It is shown that the positive equilibrium exists if predator death rate multiplied by a constants is smaller than its growth rate multiplied by capturing rate. Moreover, by constructing a Lyapunov function, it is shown that the positive equilibrium is globally stable.